The Rise of Greta Thunberg: A Case Study in Micro-Celebrity and Global Climate Mobilisation - Liu, Yichen (International Journal of Social Sciences and Public Administration, 2024)
Social media influencers can mobilise their networks widely, sharing information and adding their voices to numerous online discussion groups in the digital age. The social media identity of Swedish environmental activist Greta Thunberg is marked by authenticity, making her an important figure in current discussions about climate change and activism. This essay will discuss her identity on social media platforms and mention the challenges regarding communication strategies and goals. Also, the relationship between the content creators, audiences and platforms will be investigated. It will argue that while social media has provided influencers the opportunity to develop their identities and communicate with their audiences, it has also exposed them to a great deal of online criticism and challenges.